2016
DOI: 10.1007/s11033-016-4016-9
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic induction of placental growth factor in retinal pigment epithelial cells in vitro: contribution of NFAT5 activity

Abstract: One risk factor of neovascular age-related macular degeneration is systemic hypertension; hypertension is mainly caused by extracellular hyperosmolarity after consumption of dietary salt. In retinal pigment epithelial (RPE) cells, high extracellular osmolarity induces vascular endothelial growth factor (VEGF)-A (Hollborn et al. in Mol Vis 21:360-377, 2015). The aim of the present study was to determine whether extracellular hyperosmolarity and chemical hypoxia trigger the expression of further VEGF family memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…VEGF-D and VEGF-A had been identified to play an important role in angiogenesis. The previous study reported that the high expression of VEGF-D, in addition to VEGF-A, exacerbated the angiogenic response of retinal pigment epithelium (RPE) cell in nAMD [22]. However, as far as we know, there was few research on the concentration of VEGF-D in PCV, SD = Standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF-D and VEGF-A had been identified to play an important role in angiogenesis. The previous study reported that the high expression of VEGF-D, in addition to VEGF-A, exacerbated the angiogenic response of retinal pigment epithelium (RPE) cell in nAMD [22]. However, as far as we know, there was few research on the concentration of VEGF-D in PCV, SD = Standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF-D and VEGF-A had been identified to play an important role in angiogenesis. The previous study reported that the high expression of VEGF-D, in addition to VEGF-A, exacerbated the angiogenic response of retinal pigment epithelium(RPE) cell in nAMD [22]. However, as far as we know, there was few research on the concentration of VEGF-D in PCV, let alone the comparison of aqueous humor levels of VEGF-D in three groups, even they seldomly distinguished VEGF family such as detecting VEGF-A and VEGF-D respectively [13,16].…”
Section: Discussionmentioning
confidence: 99%
“…Taurine transporter is also involved in the osmoregulation of RPE cells subjected to HOS [ 125 ]. HOS-induced increase in aldose reductase, taurine transporter and AQP5 mRNA levels has been shown to be dependent on TonEBP/NFAT5 transactivation activity, suggesting that targeting TonEBP/NFAT5 could represent a new therapeutic strategy for the treatment of DR [ 120 , 126 , 127 ].…”
Section: What Are the Consequences Of Hos On The Rpe?mentioning
confidence: 99%
“…HOS can modify the RPE secretome by increasing the expression of VEGF [ 42 ], placental growth factor (PlGF) [ 127 ], monocyte chemoattractant protein-1 (MCP-1) [ 96 ], basic fibroblast growth factor (bFGF), and heparin-binding epidermal growth factor-like growth factor (HB-EGF) [ 134 ], interleukin 1β (IL1β), interleukin 18 (IL18), and moderately of epidermal growth factor (EGF), tumor-growth factor β1 (TGF-β1), interleukin-6 (IL6), and interleukin-8 (IL8) [ 134 ]. HOS has been shown to increase both IL1β and IL18 by inducing the priming of the Nod-like receptor protein 3 (NLRP3) inflammasome.…”
Section: What Are the Consequences Of Hos On The Rpe?mentioning
confidence: 99%